Scrabble-Mediated Collaborative Learning to Enhance Arabic Writing Skills among Senior High School Students - Kemas Muhammad; Khilda Jannati Syarifah; Jumhur Jumhur; Daud Abdul Quadir Elega (JURNAL IJ-ATL, 2026)
This study investigates the implementation of collaborative learning–based Mahārah Kitābah instruction using Scrabble media for eleventh-grade students. The scope of this research focuses on improving students’ Arabic writing skills through collaborative activities supported by educational game media. The objective of this study is to examine the effectiveness of Scrabble media in collaborative learning and to analyze students’ responses to the learning process. This research employed a quasi-experimental design involving an experimental class and a control class. Data were collected through pre-tests and post-tests, questionnaires, interviews, and classroom observations. The experimental class was taught using collaborative learning with Scrabble media, while the control class received conventional instruction. The quantitative results show that the post-test mean score of the experimental class was 77, which was higher than that of the control class with a mean score of 67. Furthermore, the independent sample t-test results indicate a significant difference between the two classes with a Sig. (2-tailed) value of 0.000, confirming the effectiveness of the treatment. Qualitative data obtained from questionnaires and interviews reveal that students responded positively to the use of Scrabble media, particularly in enhancing motivation, vocabulary mastery, collaboration, and confidence in writing Arabic. Classroom observations also demonstrate increased student participation during the learning process. In conclusion, collaborative learning–based Mahārah Kitābah instruction using Scrabble media is effective in improving students’ Arabic writing skills and fostering a more engaging learning environment.